2021
DOI: 10.3390/pharmaceutics13081122
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Preparation Method on the Properties of Orodispersible Films with Aripiprazole: Electrospinning vs. Casting and 3D Printing Methods

Abstract: Orodispersible films (ODFs) address the needs of pediatric and geriatric patients and people with swallowing difficulties due to fast disintegration in the mouth. Typically, they are obtained using the solvent casting method, but other techniques such as 3D printing and electrospinning have already been investigated. The decision on the manufacturing method is of crucial importance because it affects film properties. This study aimed to compare electrospun ODFs containing aripiprazole and polyvinyl alcohol wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…With the addition of the drug or when blended with PVP or PVA, toughness and breaking elongation decrease. Obtained results for blended films F3 and F5 are in agreement with literature data [39,44,54]. The tensile tests revealed that F6 showed 30% lower tensile strength and 11% higher modulus of elasticity than F4.…”
Section: Tensile Testsupporting
confidence: 88%
“…With the addition of the drug or when blended with PVP or PVA, toughness and breaking elongation decrease. Obtained results for blended films F3 and F5 are in agreement with literature data [39,44,54]. The tensile tests revealed that F6 showed 30% lower tensile strength and 11% higher modulus of elasticity than F4.…”
Section: Tensile Testsupporting
confidence: 88%
“…The moisture content depends on the material of the film and the method used in the production, but it is mostly within the range of 3–11%. Łyszczarz et al obtained 2.8% of moisture content for ODFs prepared by electrospinning, 7.9% for 3D printed films and 10.9% for casted ODFs [ 38 ]. These films were prepared from an aqueous solution of polyvinyl alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis of commercial products shows that the tensile strength should be at least 30 N/cm 2 [44,46]. The ODFs loaded with quetiapine in a different study show much smaller tensile strength values (2.12-3.65 N/cm 2 ) and percentual elongation of 5.01-6.33% [47].…”
Section: Tensile Testingmentioning
confidence: 99%